O acesso às tecnologias reprodutivas: garantias e limites jurídicos - Aldrovandi, Andrea (My University, 2014)
The present study is concerned with the guarantees and judicial limits to the access to the techniques of assisted human reproduction in Brasil. The reproductive technologies can be used for the benefit of individual who intends to conceive a child, aiming the prevention of diseases and to execute the parental project, constituting an available method for the projection of the reproductive life. In front of this, its access finds shelter in the right to the health, and in the sexual and reproductive rights, which were added in our ordainment through the constitutional forecast of the right to the familiar projection, recognizing the autonomy of every person to decide on their reproductive life. However, the national panorama shows that these rights are not respected in practice, because in our country. This situation is worsened by the lack of a special legislation which establishes directrixes and principles that are action imitators and represent the infringement of the human dignity, as much the beneficiaries, as the child who will be procreated. For this, it is outstanting the necessity of the approval of a special legislation that responds to the fast progress of the medicine and biotechnology and to the challenges which come from its application over the man. This law must be based on the discussions of the bioethic and on the bioright to establish principles which permit the advance of the science, inciting the solidarity and conscious and responsible decisions, preventing the intervention of the science over the human life not to cause infringement of the valves which constitute the person s nature.
O presente estudo trata das garantias e limites jurídicos ao acesso às técnicas de reprodução humana assistida no Brasil. As tecnologias reprodutivas podem ser utilizadas em benefício do indivíduo que pretende gerar um filho, com o objetivo de prevenção de doenças e para realizar o projeto parental, constituindo método disponível para o planejamento da vida reprodutiva. Diante disso, o seu acesso encontra guarida no direito à saúde, e nos direitos sexuais e reprodutivos, que foram inseridos em nosso ordenamento por meio da previsão constitucional do direito ao planejamento familiar, reconhecendo a autonomia de toda pessoa de decidir sobre sua vida reprodutiva. Contudo, o panorama nacional demonstra que esses direitos não são respeitados na prática. Essa situação é agravada pela ausência de uma legislação especial que estabeleça diretrizes e princípios limitadores de ações que representem a violação da dignidade humana, tanto dos beneficiários, quanto da criança que será gerada. Para tanto, destaca-se a necessidade de aprovação de uma legislação especial que responda ao rápido progresso da medicina e da biotecnologia e aos desafios advindos de sua aplicação sobre o homem. Esta lei deve basear-se nas discussões da bioética e no biodireito, para estabelecer princípios que permitam o avanço da ciência, estimulando a solidariedade e decisões conscientes e responsáveis, sem que a intervenção da ciência sobre vida humana acarrete na violação de valores que constituem a essência da pessoa.
Keywords: Direitos especiais; Reprodução assistida; Planejamento familiar; Acesso; Dignidade humana; Assisted reproduction; Familiar projection; Access; Human dignity; Tecnologias reprodutivas; Reproductive technologies